2023
DOI: 10.1007/s11695-022-06436-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Matched Comparison of Primary and Revisional Laparoscopic Sleeve Gastrectomy

Abstract: Background Reports of long-term (> 5–15-year) outcomes assessing the safety and efficacy of primary revisional laparoscopic sleeve gastrectomy (LSG) are few. Methods Retrospective long-term comparisons of primary (pLSG) and revisional (rLSG) procedures were matched for gender, age ± 5 years, and body mass index (BMI) ± 5 kg/m 2 . Weight loss, associated medical condition status, and patient satisfaction were evaluated. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(46 reference statements)
0
5
2
2
Order By: Relevance
“…A long-term retrospective cohort study [ 41 ] found significantly higher percent excess BMI lost in the RLSG group at 6 years and 9 years follow-up. In contrast, a recent cross-matched study [ 42 ] found significant higher %EWL in the PLSG group in the short-term but similar %EWL between both groups in the long-term. However, the long-term results may have been influenced by the significant differences in follow-up durations between both groups [ 42 ].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A long-term retrospective cohort study [ 41 ] found significantly higher percent excess BMI lost in the RLSG group at 6 years and 9 years follow-up. In contrast, a recent cross-matched study [ 42 ] found significant higher %EWL in the PLSG group in the short-term but similar %EWL between both groups in the long-term. However, the long-term results may have been influenced by the significant differences in follow-up durations between both groups [ 42 ].…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast, a recent cross-matched study [ 42 ] found significant higher %EWL in the PLSG group in the short-term but similar %EWL between both groups in the long-term. However, the long-term results may have been influenced by the significant differences in follow-up durations between both groups [ 42 ]. Regardless, the long-term differences in WL efficacy between RLSG after GB and PLSG are unknown due to the lack of large, long-term, matched studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Comparison of primary and revisional MBS has been reported in the literature. Sakran et al [27] evaluated the long-term outcomes (12 years) of patients undergoing primary versus revisional SG, and it was shown that mean TWL was comparable between groups (20.9 and 18.3; p = 0.165) and resolution of associated medical conditions was comparable as well. Despite showing these outcomes, Long-Term Outcomes of Primary versus Revisional One Anastomosis Gastric Bypass Obes Facts 2024;17:303-310 DOI: 10.1159/000538768 more than 50% had insufficient weight loss and the vast majority of patients in both groups had weight regain with a trend toward earlier weight regain in the revisional group (2.6 vs. 3.4 years).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Some studies tend to show a positive effect of RBS on the treatment of T2DM, regardless of the surgical sequence. 9 , 11 , 12 However, this body of evidence mainly relies on studies compiling heterogeneous data or with a small sample size and would need to be strengthened.…”
Section: Introductionmentioning
confidence: 99%